Legal Validity and Implications of Remarriage During Divorce Proceedings in Indonesia: An Islamic Family Law Perspective - Annisa Rahmi; Nurul Huda Prasetiya (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
This study examines the phenomenon of unregistered marriages (sirri) conducted by women who are still undergoing divorce proceedings at the Religious Court of Teluk Nibung. The primary objective is to analyze the legal status of such marriages from the perspective of Islamic law and Indonesian positive law. Employing a qualitative method with a juridical-empirical approach, the research draws on interviews, observations, and document analysis. The findings indicate that remarriage during an unresolved divorce process is driven by socio-economic factors, spousal neglect, and limited legal awareness. From the standpoint of Islamic jurisprudence, particularly within the Shafi’i and Hanbali traditions, such marriages are invalid because the woman is not yet considered a widow in the sharī‘ah sense and has not completed the prescribed iddah period. Under Indonesian statutory law, these practices contravene the principle of monogamy as enshrined in Law No. 1 of 1974 and the Compilation of Islamic Law. This study highlights the incompatibility of the practice with both normative frameworks and underscores the urgent need for legal education and stronger institutional oversight to prevent deviations. The research contributes to the discourse on marriage law by offering a socio-legal perspective that integrates doctrinal analysis with community realities.